2015
DOI: 10.1111/mec.13375
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of Oryza rufipogon and Oryza nivara: implications for the origin of O. nivara

Abstract: Ecological speciation plays a primary role in driving species divergence and adaptation. Oryza rufipogon and Oryza nivara are two incipient species at the early stage of speciation with distinct differences in morphology, life history traits and habitat preference, and therefore provide a unique model for the study of ecological speciation. However, the population genetic structure of the ancestral O. rufipogon has been controversial despite substantial study, and the origin of the derivative O. nivara remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 86 publications
10
44
0
1
Order By: Relevance
“…1). This is consistent with the results of Liu et al (2015), who found no correlation between genetic groups and geographic regions in wild rice, and ascribed the absence of a phylogeographic pattern to repeated extinctions and re-colonizations of wild populations during Quaternary glacial-interglacial cycles. If this explanation is correct, it may imply that both mutations emerged prior to the last glaciation.
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…1). This is consistent with the results of Liu et al (2015), who found no correlation between genetic groups and geographic regions in wild rice, and ascribed the absence of a phylogeographic pattern to repeated extinctions and re-colonizations of wild populations during Quaternary glacial-interglacial cycles. If this explanation is correct, it may imply that both mutations emerged prior to the last glaciation.
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…Previous studies of genome-wide polymorphism have clustered aus and indica together (Garris et al 2005; McNally et al 2009; Xu et al 2011), however, none have specifically tested whether aus and indica have a single or separate origins. Our results suggest that japonica , indica , and aus have their origins in distinct ancestral populations, consistent with phylogeographic studies that show population structuring and geographic subdivision within O. rufipogon , with O. nivara as a separate group (Sun et al 2002; Huang et al 2012a; Huang et al 2012b; Liu et al 2015). …”
Section: Discussionsupporting
confidence: 90%
“…Aquilegia species are mainly outcrossed by different pollinators and the genetic diversity data from this study, together with other research, provide a good example for investigating how different mating systems and pollinators influence the nucleotide polymorphism between species. We also found that the genetic diversity at the species level was significantly higher than at the population level; this pattern has been reported in other research, such as A. thaliana , Oryza rufipogon Griff., O. nivara S. D. Sharma & Shastry, and Zea mays L. (Moeller & Tiffin, ; Nordborg et al, ; Liu et al, ). We suspected that the population structure might be responsible for this because segregating sites emerged when highly structured populations were put together.…”
Section: Discussionmentioning
confidence: 99%